Agenesis of Internal Carotid Artery and Ischemic Stroke, One Case Report: A Review of Literature - Mapaga Nyangui, Jennifer; Martinez, Mikel; Desbordes, Patrice; Diawarai, Alpha; HOUEZE, Richard; C. Laurenti, C. Laurentr; Jacquin, Julien (My University, 2018)
Background: Agenesis of the internal carotid artery (ICA) is a rare anatomic variation of the cerebral circulation. A malfunction during the embryonic period is at stake. It is very often asymptomatic and therefore discovered incidentally. Association with ischemic stroke is exceptional. Physio pathology is uncertain; the hypothesis of a blood flow reversal is reported in the literature. The diagnosis is based on the absence of a carotid canal as revealed by CT scans at skull base level with bone settings. Other non-invasive techniques, including echo-Doppler of the neck vessels, can now make the diagnosis. Objective: Discuss the association between occurrence of an ischemic stroke in the left posterior sylvian territory and discovery of ipsilateral carotid agenesis. Case report: A 24-year-old female patient was prospectively recruited at DAX hospital center (France). Vascular risk factors involved active smoking of 8 pack-years and a combined estrogen/progestin contraceptive. Her family history included an uncle with heterozygote Factor V Leiden mutation. She presented a left upper limb sensorimotor deficit. Nuclear Magnetic Resonance Angiography (MRA) revealed a right superficial sylvian ischemic stroke associated with agenesis of the right internal carotid artery. CT scan at skull base level with bone settings showed absence of a right carotid canal, thus confirming agenesis. An opinion was then requested for an arteriography which showed an operative polygon of Willis, a sylvian artery or middle cerebral artery (MCA) irrigated by a very large right posterior communicating artery (PCOM) and the left anterior cerebral artery (ACA) supplied by the anterior communicating artery (ACOM), through the left carotid system. The right sylvian territory where stroke occurred was therefore supplied by the functional vertebrobasilar system. ECG and four-day meticulous monitoring detected no cardiac rhythm disorders. Transesophageal echocardiography was normal. Blood tests results showed normal blood coagulation with glycohemoglobin level at 4.6%. Total cholesterol was 1.42 g/l including LDL-C at 0.82 g/l and HDL-C at 0.36 g/l; triglycerides levels were 1.23 g/l. VDRL-TPHA serodiagnosis for syphilis, and HIV serology were all negative. Thrombophilia testing was performed and showed absence of Factor V Leiden mutation. Homocysteinemia level was normal. The patient was discharged under KARDEGIC 160 mg, one daily with home rehabilitation. Currently she’s doing well and no recurrence is observed.
Keywords: Right Internal Carotid Artery Agenesis; Ischemic Stroke; Rare